Major Paths Changes In 2013-2022 To Walkability (Case Study: Dukuh Atas TOD) - Tulis, Daniel Harvey; Sihombing, Antony (Smart City, 2023)
Development area with the concept of Transit Oriented Development (TOD) occurs so rapidly in big cities, which aims to create an integrated transportation system and is supported by the surrounding area. TOD area must have good road access for vehicles and space for pedestrians. Dukuh Atas TOD is one of the transit-oriented areas planned to be the largest TOD area in Jakarta so that developments are felt every year, including visuals and the road traffic system and pedestrian space. This research is using qualitative method by answering specific and actual variables. Time series analysis to see changes every year combined with figure-ground analysis in mapping the location of changes that occur and will be described. The research results will produce an overview of road changes in the study period and knowledge of road construction and pedestrian space suitability based on predetermined standards. Visual changes, traffic systems, and pedestrian space will be the variables of this study is needed to see applicable standards, or any changes that are inappropriate that planning is needed to align with the function of the road as a connecting and as social activities in the area around Dukuh Atas TOD.